2019
DOI: 10.1103/physrevb.99.184301
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature anharmonicity and the thermal conductivity of cesium iodide

Abstract: Cesium halide has a simple cubic crystal structure and hosts low thermal conductivity, but its microscopic mechanism has not been fully understood. In the present work, we took cesium iodide (CsI) single crystal as an example, to investigate the lattice dynamics and thermal conductivity by performing inelastic neutron scattering (INS), heat transport measurements and the first-principles calculations. The temperature dependent phonon dispersions of CsI were obtained from INS and the low temperature anharmonici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…2 shows the calculated phonon dispersions for all studied compounds, which agree well with available experimental data. [7,29,[47][48][49][50][51][52][53][54][55][56] The general shape of phonon dispersions in NaCltype (Figs. 2a-i) and CsCl-type (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 shows the calculated phonon dispersions for all studied compounds, which agree well with available experimental data. [7,29,[47][48][49][50][51][52][53][54][55][56] The general shape of phonon dispersions in NaCltype (Figs. 2a-i) and CsCl-type (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…[3] These prominent properties associate closely with phonon thermal transport properties, such as lattice vibrations [4][5] and thermal conductivities. [6][7] For most compounds in alkali halides, the thermal conductivities are relatively low, and the values at room temperature range from 1 to 7 W/mK. [8] Previous works have been performed to investigate the thermal properties of alkali halides using classical theoretical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-quality GaN single crystals (un-doped, n-type, MTI Corporation [36]) used in this work were grown by the hydride vapor phase epitaxy (HVPE)-based method with low dislocation density (< 1  10 7 cm -2 ) (Fig. S1c).…”
Section: Gan Single Crystal Samplesmentioning
confidence: 99%
“…For example, in the leading thermoelectric material SnSe, it was recently found that the coupled instability of electronic orbitals and lattice dynamics is the origin of its strong anharmonicity and ultralow thermal conductivity [39,48]. In the typical ionic compound, cesium halides (e.g., CsCl, CsBr, and CsI), a lowtemperature anharmonicity was found with anharmonic Cs displacements and short phonon lifetime, compared with the anharmonic behavior commonly occurring at higher temperatures [49,50]. The remarkable progress of phonon an-harmonicity promotes a deep understanding of thermoelectrics [39,46,48], ferroelectrics [51,52], multiferroics [53][54][55], high-T c superconductors [56][57][58], etc.…”
Section: Introductionmentioning
confidence: 99%